(untitled) (Journal of the Medical College for Women & Hospital, 2025)
Background: Systemic lupus erythematosus (SLE) is an autoimmune connective tissue disease of variable severity. Multisystem organ involvement and tissue damage in SLE is mediated by production of autoantibody, disposition of immune complex and abnormal activation of complement pathway. This study was designed to investigate the thyroid dysfunction and its association with active disease in patients with SLE. Materials and method: This cross-sectional study was conducted in the Department of Physiology, Dhaka Medical College, Dhaka from July 2016 to June 2017. For this study, 30 SLE patients aged 18 to 55 years with duration of disease ≤5 years were included. Thyroid function test was estimated. Z Proportion test and Binominal regression analysis were performed as applicable. p value <0.05 was accepted as level of significance. Results: In this study, median, interquartile range (IQR) TSH was 4.1 (2.4-7.4) IU/L, FT3 was 4.1 (3.0-4.5) pmol/L and FT4 was 12.6 (8.2-14.0) pmol/L. About 26.7% patients had hypothyroidism and 6.7% had hyperthyroidism. Hypothyroidism was significantly (p=0.012) higher in active SLE and 2 times (95% CI: 1.317 to 3.037) more risk for development of active disease in SLE. Conclusion: This study concludes that hypothyroidism is more likely to occur in SLE patients. It is significantly associated with active SLE. J Med Coll Women Hosp.2025; 21 (1):52-57